District level analysis of routine immunization in Haryana State: Implications for mission indradhanush under universal immunization programme - Shankar Prinja; Divya Monga; Saroj Kumar Rana; Atul Sharma; Suresh Dalpath; Pankaj Bahuguna; Rakesh Gupta; Arun Kumar Aggarwal (Wolters Kluwer Medknow Publications, 2018)
Background: The immunization coverage in India is far away from satisfactory with full immunization coverage being only 62% at national level. Targeting the intensive efforts to poor performing areas and addressing the determinants of nonimmunization and dropouts offers a quick solution. In this paper, we assess the inter-district variations in Haryana state, and the association of social determinants with partial and no immunization. Methodology: This analysis is based on data collected as part of a large household survey undertaken in the state of Haryana to measure the extent of Universal Health Coverage. A multistage stratified random sampling design was used to select primary sampling units (i.e., subcenters), villages, and households. A total of 11,594 mothers with a child between 12 and 23 months were interviewed on receipt of immunization services. Determinants of nonimmunization and partial immunization were assessed using multiple logistic regression. Results: About 21% of children aged 12-23 months were partially immunized, while 4.3% children aged 12-23 months had received "no immunization." While the coverage of full immunization was 74.7% at the state level, it varied from 95% in best performing district to 38% in poorest performing district. Odds of a partially immunized child were significantly higher in urban area (odds ratio [OR] = 1.23; 95% confidence interval [CI] = 1.1-1.38), among Muslim household (OR = 3.52; 95% CI = 3.03-4.11), children of illiterate parents (OR = 1.58; 95% CI = 1.22-2.05), and poorest quintile (OR = 1.61; 95% CI = 1.36-1.89). Conclusions: Wide interdistrict variations call for a need to consider changes in resource allocation and strengthening of the government initiatives to improve routine immunization in these districts.